Modelling the Effects of Element Doping and Temperature Cycling on the Fracture Toughness of β-NiAl / α-Al2O3 Interfaces in Gas Turbine Engines - Tyler, Samson (Université d'Ottawa / University of Ottawa, 2013)
This document describes work performed related to the determination of how elemental additions affect the interfacial fracture toughness of thermal barrier coatings at the bond coat/thermally grown oxide interface in gas turbines. These turbines are exposed to cyclical thermal loading, therefore a simulation was designed to model this interface in a temperature cycle between 200 K and 1000 K that included oxide growth between 2 μm and 27 μm. The fracture toughness of this interface was then determined to elucidate the function of elemental additions. It was shown that minimal concentrations of atomic species, such as hafnium and yttrium cause notable increases in the toughness of the bond coat/thermally grown oxide interface, while other species, such as sulphur, can dramatically reduce the toughness. Furthermore, it was shown that, contrary to some empirical results, the addition of platinum has a negligible effect on the fracture toughness of this interface.
Keywords: Fracture; Toughness; Interface; NiAl; NiPtAl; Modelling; Alumina; Buckling; Spallation; Turbine; Thermal Barrier Coating; Doping; Adhesion; Residual Stress